Sha Lin Fashion / Nurshakina Azlin Khairul Ariffin - Khairul Ariffin, Nurshakina Azlin (2020)
Sha Lin Fashion Boutique is a form of business based on a partnership consisting of five members who hold important positions such as General Manager, Production Manager, Design Manager, Administration Manager and Marketing Manager. This Sha Lin Fashion boutique provides shirts and the like with various designs using quality fabrics according to the suitability of each customer.Sha Lin Fashion is located in Sha Lin Fashion, No. 2, Persiaran Pusat Bandar Putra Point, Putra Nilai, 71800 Nilai, Negeri Sembilan. Sha Lin Fashion is a company that focuses on the production of clothing for both women and men in Malaysia. This boutique provides various clothing designs that customers want nowadays because they are comfortable to wear and suitable to wear anywhere. The difference between regular clothes compared to the clothes created by our company and boutique makes this design look more attractive and suitable for all sizes for all customers. To make it even more interesting, we decided to create some creativity and innovation by implying creativity and modern elements in each of these outfits. We have done some research that Malaysia is a developed country made up of people with low income levels and higher income levels. Therefore, we recommend clothes in this Sha Lin Fashion Boutique to suit all types of income levels because the prices in our Boutique are reasonable and affordable for every customer who comes.